Engaging and Empowering Parents of Children with Down Syndrome-The Role of Parents Support Group - Abdul Wahab, Asrul; Md. Monoto, Ezura Madiana (IIUM Medical Journal Malaysia, 2018)
Children with Down syndrome are known to have intellectual disability, developmental milestone delay and may also have associated medical conditions. Having a child with Down syndrome could be physically and emotionally challenging to the affected family members. The impact on a family can be multifaceted which can alter the family dynamics and harmony. Most parents felt inadequate with the information given by the healthcare providers. Parents support group plays an important role to support and provide information and resources to other parents of children with Down syndrome. The knowledge and experience on raising the children with Down syndrome are shared with the new parents. This includes the importance of Early Intervention Program (EIP), inclusive education, the benefits of People with Disability card, sharing success story of people with Down syndrome and providing emotional support to the family to boost their confidence and keeping up their positive spirit in raising their children, regardless of their religions and beliefs. Apart from that, we also organize and participate in activities to raise public awareness, advocating for the rights, inclusion and well being of people with Down syndrome, through social and mass media and annual celebration of World Down Syndrome Day on the 21st March. We promote the benefits of inclusive environment so that people with Down syndrome are able to enjoy full and equal rights on an equal basis with other people; enabling them to live, work and participate with confidence and individual autonomy, fully included in society alongside their friends and peers. As healthcare professionals and parents of a child with Down syndrome, we are sharing our own experiences in engaging with other parents of children with Down syndrome to understand the issues and concerns, sharing resources available around them and ways to support them throughout the journey of raising a child with Down syndrome.